Crossing the sea : narratives of exile and illness among Cambodian refugees in New Zealand : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Social Anthropology at Massey University - North, Nicola H.; North, Nicola H. (Massey University, 1995)
Cambodian refugees have settled in many countries of the West, including New Zealand. Cambodian refugees are consistently described as the most traumatised of Southeast Asian refugees; hence they are expected upon resettlement to be in special need of health care, which host countries must provide. Most Cambodians from rural areas have had little prior experience with Western-type health care, having employed mainly local (rural Cambodian) healing techniques, supplemented with a range of available Western and Asian medicines, in an environment of medical pluralism. Using the ethnographic method, this three year study set out to determine illness experiences of resettled Cambodian refugees, and to interpret experiences in the contexts of the events that led to their fleeing Cambodia, the trauma of the flight itself, and the process of resettlement in an unfamiliar nation, geographically and culturally far distant from home. Theories that Cambodians hold regarding the origins, progress, and preferred treatments of illness are described. Experiences of seeking health care from New Zealand's biomedically based health services are presented, and complementary health-care practices such as Cambodian self-care and alternative medicines are identified. Adult Cambodian who have survived severe deprivation, atrocities and profound loss often suffer serious ill health. Ill health is both cause and consequence of inability to acquire new skills and education, low facility in English, unemployment and poverty. For adults caught in the cycle of illness and poverty, social interaction is primarily with other Cambodians. A Cambodian sub-society on the margins of mainstream society has emerged, in which, among other things, healing practices are carried out. Cambodian refugees show no reluctance to use Western medicine, and little desire to employ Cambodian medicine, which in any case is now largely unavailable. While some Cambodians suffer from diseases that appear amenable to Western medical diagnoses and treatments, others have been found to suffer intractable, often painful illnesses for which no biomedical explanation could be found. In such cases, the sufferers themselves offered explanations for their illnesses, drawing from Cambodian theories of illness, and personal life experiences, in doing so. However, some serious illnesses experienced by Cambodian refugees fit neither Cambodian nor Western biomedical disease categories. A result of exile is that familiar Cambodian systems of healing are no longer relevant, and at the same time, conditions of exile and transition cast doubt on former theories of illness, leading to a search both for understanding and for healing. Employing Cambodian self-care techniques together with Western and Asian medicines, resettled Cambodians are actively creating a transitional system of healing appropriate to their transitional status. Hard, solitary intellectual labour ("thinking too much") is a central process by means of which exiled Cambodians struggle to regain control of their shattered lives. The development of a new system of healing is part of the global process of hybridization of cultures, accelerated by massive transnational migration. To depict both the danger and the generativity of the transformations of which Cambodian refugees are both agents and subjects, the study concludes by borrowing a Cambodian metaphor for giving birth: "crossing the river." Cambodians consider women post-childbirth to be weakened and vulnerable to illness, cold and wind; while the child is newly born into humanity, the mother too is reborn into a new social status. Refugees who have literally crossed the sea to settle in a new country are undergoing a similar rebirth.
Keywords: Southeast Asian refugees; Cambodian health care; Resettlement; Alternative medicine; Traditional health care; Acculturation; Traditional medicine